- #1

- 81

- 0

The difference between their reciprocals is 1/90

What are the two numbers?

I worked out that:

x-y=3 and

1/x-1/y= 1/90

Is that right so far?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Paulo2014
- Start date

- #1

- 81

- 0

The difference between their reciprocals is 1/90

What are the two numbers?

I worked out that:

x-y=3 and

1/x-1/y= 1/90

Is that right so far?

- #2

- 1,752

- 1

yes, keep going

- #3

- 81

- 0

I don't have a clue what to do next

- #4

malawi_glenn

Science Advisor

Homework Helper

- 4,786

- 22

When you have two equations of two unkowns, the strategy is to express one of the unkowns as a "function" of the other unknown.

e.g

y+2x=9 gives: y = 9 -2x

Then substitue that into the other equation.

- #5

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 963

NO! If x- y= 3, aThe difference between two positive numbers is 3.

The difference between their reciprocals is 1/90

What are the two numbers?

I worked out that:

x-y=3 and

1/x-1/y= 1/90

Is that right so far?

Now you know that y= x- 3 so 1/(x- 3)- 1/x= 1/90. I would recommend multiplying that every term in that equation by 90x(x-3) in order to get rid of the fractions.

By the way, it is always a good idea to start a problem like this, NOT by saying "x- y= 3" but by

Last edited by a moderator:

- #6

- 81

- 0

- #7

- 238

- 0

You multiply by 90x(x-3) in order to cancel the terms in the denominator, making it easier to solve for x.

- #8

- 52

- 0

a: x - y = 3

b: 1/y - 1/x = 1/90

What *I* would do if I'm a rookie is multiply equation b by x*y*90 since that is the LCM of the denominators and I'm scared of fractions. This would give me:

b*: 90x - 90y = xy

at this point you can use the substitution method to solve.

HallsofIvy had a slightly different approach which comes with training. First he solved eqn a for y. ie a*: y = x -3. Then he substituted this into equation b to get:

b*: 1/(x-3) - 1/x = 1/90

now the LCM of the denomiators is x * (x-3) * 90. If you mulitply by that you get:

b**: 90x - 90(x-3) = x(x-3)

If you follow the first method, you'll see that both methods turn out to be the same, except that my way is easier because I got rid of all fractions before doing any work. After some "training" though, you get used to the fractions, and just solve without getting rid of them the second you see them.

I think the biggest lesson to take away from this is be sure to label your variables at the beginning! So I'm double emphasizing it =)

Share: